Recurrence of retroperitoneal localized perivascular epithelioid cell tumor two years after initial diagnosis: case report - Cihan, Yasemin Benderli (2019)
CONTEXT: Perivascular epithelioid cell tumors (PEComas) are rare mesenchymal tumors. Adjuvant radio-therapy and/or chemotherapy are administered according to the patient’s clinical characteristics. CASE REPORT: A 42-year-old female patient was operated to treat a retroperitoneal mass. The diagnosis was established as PEComa with benign behavior. Two years after the diagnosis, chest and abdominal computed tomography scans showed intra-abdominal recurrence and lymphangioleiomyomatosis in the lung. Treatment with everolimus was started. The disease stabilized in the third month of treatment, ac-cording to the response evaluation criteria in solid tumors. CONCLUSION: PEComas are tumors with unpredictable behavior. Therefore, these patients require long-term follow-up, even in cases of correct diagnosis and benign PEComa.